Physiological and psychological effects of heat exposure among steel industry workers - Izzati, Isahak (2018)
Exposed to hot working environment can results in variety of heat-related illness and safety problems. A study of physiological and psychological effects of heat exposure among steel industry workers was conducted in a steel industry located in Gebeng, Kuantan, Pahang. This study involves 20 steel industry workers who were exposed to heat sources. The purpose of this study are to determine the physiological (body temperature and heart rate) and psychological (fatigue feeling) effects of workers when they are exposed to sources of heat in hot working environment. The factors that contribute to heat exposure among the workers were identified first. After that, the relationship between physiological and psychological effects experienced by the workers with the exposure to heat sources is determined. The finding of this study reveals that the factors of heat exposure among the workers, which are air temperature or Wet Bulb Globe Temperature (WBGT) indoor, relative humidity, and air velocity were above acceptable range recommended by Industry Code of Practice Indoor Air Quality, DOSH Malaysia (2010) and also exceeded Permissible Heat Exposure Threshold Limit Value (TLV) recommended by ACGIH (2008). Besides that, it has been found that physiological indices of the workers which are body temperature and heart rate, shows an increment after they exposed to heat sources. There are significant differences between body temperature before and after working (p=0.003). However, for heart rate, the increment is not significant (p=0.838). Majority of the workers feel fatigue when exposed to heat sources, but they still can proceed work. Furthermore, the relationship between body temperature with WBGT indoor are weak (r = 0.268, p > 0.05). However, the relationship between heart rate with WBGT indoor are strong (r=0.543, p<0.05). Meanwhile, the relationship between WBGT indoor with fatigue feeling experienced by the workers is weak (r= -0.119, p>0.05). The results obtained prove that physiological changes happen when workers exposed to hot working environment.